Revision surgery after rod breakage in a patient with occipitocervical fusion: A case report. Issue 15 (April 2018) - Tang, Chao; Li, Guang Zhou; Kang, Min; Liao, Ye Hui; Tang, Qiang; Zhong, De Jun
Abstract: Rationale: Rod breakage after occipitocervical fusion (OCF) has never been described in a patient who has undergone surgery for basilar invagination (BI) and atlantoaxial dislocation (AAD). Here, we present an unusual but significant case of revision surgery to correct this complication. Patient concerns: A 32-year-old female presented with neck pain, unstable leg motion in walking, and also BI with AAD. Her first surgery was planned to correct these conditions and for fusion at the occipital junction (C3-4) using a screw-rod system. At the 31-month follow-up after her first operation, the patient complained of severe neck pain and limitation of motion, suggesting rod breakage. Diagnoses: Rod breakage after occipitocervical fusion for BI and AAD. Interventions: The patient underwent reoperation for replacement of the broken rods, adjustment of the occipitocervical angle, maintenance of the bone graft bed, and fusion. Outcomes: At follow-up, the hardware was found to be in good condition, with no significant loss of cervical lordosis. At the 37-month follow-up after her second operation, the patient was doing better and continuing to recover. Lessons: We concluded that nonideal choice of occipitocervical angle may play an important role in rod breakage; however, an inadequate bone graft and poor postoperative fusion may also contribute to implant failure.